The effect of visfatin genotype on insulin pump therapy on quality of life in patients with type I diabetes - Jianjun, Lv; Xiaona, Liu; Hong, Li (Cellular and Molecular Biology, 2022)
Diabetes is associated with an increase in other chronic diseases and an increase in mortality. The individual differences influence the treatment of this disease in pharmacokinetics and clinical responses. One of the important factors related to individual differences includes genetic factors in transmission, metabolism, and drug function. On the other hand, this disease has a significant impact on the patients’ quality of life and their family. Therefore, this study aimed to investigate the role of single nucleotide polymorphism (rs2110385) of the visfatin gene on insulin required to maintain glucose homeostasis and to evaluate the effect of insulin pump therapy on the quality of life in type 1 diabetic patients. In this regard, this study was performed on 47 patients with type 1 diabetes. The short form of the Diabetes Quality of Life Questionnaire (DQOL) was used to record information. Laboratory tests also included FBS, HbA1C, G2h, serum levels of visfatin, insulin, and adiponectin. Insulin resistance (HOMA) and insulin sensitivity (QUICKI) indices were calculated. The polymorphism of the studied genotype was performed by the PCR-RFLP method. The results showed that the scores of both dimensions of quality of life, including patient care behaviors and satisfaction with the disease control after the intervention increased significantly (P <0.001). There was a significant and direct relationship between the patient’s age and the duration of the disease with the score of increasing patients’ quality of life. No significant differences were found between HbA1C, G2h, FBS levels, fasting insulin concentration, HOMA, and QUICKI indices. The insulin dose used to maintain glucose homeostasis at the same levels was significantly lower in the GG genotype than in other genotypes. In general, the present study results showed that insulin pump therapy and its dimensions could improve the life quality of patients with type 1 diabetes. Also, genetic evaluation of individuals helps to provide the correct and accurate dose of insulin with the help of the insulin pump for these patients to increase their quality of life as much as possible.